Multicomplex Uang Panai’ terhadap Perempuan dalam Perkawinan Keluarga Muslim Suku Bugis - Fitriyani, Fitriyani (STAINI Press, 2022)
The high panai' money in the marriage of the Bugis people can cause muticomplex to the family in the form of positive and negative implications. This paper aims to explore two perspectives due to the high amount of Panai' money, namely from the philosophical and sociological aspects. Using a qualitative research methodology sourced from data about Uang Panai' in traditional Bugis marriages, history books, dictionaries, journals, and articles. In addition, posts on social media such as YouTube, Instagram, Facebook, and WhatsApp. Then copy and collect them based on the theme following the research question. The researcher then analyzes the clarified data by building a coherent narrative and interpretation. This study reveals the positive impact of high Uang Panai' festive wedding party, increasing social status, and increasing popularity value. The negative impact is the rise of elopement, unregistered marriage, old virgins, financial shortages after marriage, and subordination of women. This study recommends the need for a more massive quantitative study for social acceptance and mapping of the Uang Panai' tradition in the Bugis.